(untitled) (Fiep Bulletin - online, 2014)
The direct human evaluation method is the only one obtains a result without contestation but is necessary the analysis in corpses. Throughout history a total of only 34 corpses is evaluated for the direct method and this corpses based the composition of the indirect and doubly indirect methods, for a intangible population of individuals in all world. This imbalance is increased because the searched population was of a determined ethnic group of one continent one in one determined time. This imprecision in the selection of the research increases of abrupt form when if remember that all the research guided in the direction to quantify for the direct method these relations between the corporal composition and the weight of the individual, was constructed on of individuals of advanced age, that is, a group of total diverse study of the profile of the pertaining to school group. For use of these anthropometric measures in the pertaining to school environment where in its majority they are individuals in growth phase these relations are well distant of the reality.